ON THE ROLE OF DIGITAL TECHNOLOGIES IN THE EDUCATION SYSTEM - Tursunboyev , Olmos Vaxob o‘g‘li (Innovative Development in Educational Activities, 2023)
This article deals with the role of digital technologies in the higher education system based on an analysis of their This article deals with the role of digital technologies in the higher education system based on an analysis of their capabilities. The widespread use of digital technologies in the organization of the educational process makes it possible to develop the integration of modern information and communication technologies and educational technologies, to create additional conditions for the continuous development of the professional skills of teachers. capabilities. The widespread use of digital technologies in the organization of the educational process makes it possible to develop the integration of modern information and communication technologies and educational technologies, to create additional conditions for the continuous development of the professional skills of teachers.